Myse en abyme in "Dream of the Red Chamber" - Aragón Molina, Santiago (Tropelías: Review of Literary Theory and Comparative Literature, 2025)
Dream of the Red Chamber is written with a clear awareness of creating a new novel that goes against the previous literary works of its generation, much like Cervantes’ novel Don Quixote, written against chivalric novels. These similarities extend further, touching upon the very essence of novelistic discourse and the tension it engenders. Just as Cervantes possessed a deep understanding of Spanish society of his time, Cao Xueqin was also intimately familiar with life in the palaces of China in his era, having lived in one during his youth. However, both Cervantes and Cao Xueqin do not intend for their novels to be mere reflections of the reality of their time but conceive of them also as invented artistic creations. The focus of this study centers on one of the narrative devices shared by both novels: the found manuscript. In Dream of the Red Chamber, the found manuscript contains mirrored stories (mise en abyme) of tales within other tales, a technique also present in Don Quixote. However, it is important to note that this similarity does not imply mere imitation but rather a creative exploration that enriches the narrative fabric of both works.